ADVANCEMENTS IN THE PRODUCTION OF HIGH-STRENGTH CAST IRON ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the recent advancements in the production of high-strength cast iron, a versatile material widely employed in various industries. The composition, types, and production techniques, including inoculation, nodularization, alloying, and advanced molding, are discussed. Emphasis is placed on the impact of heat treatment processes and innovative casting methods on refining the microstructure and enhancing mechanical properties. The applications of high-strength cast iron across automotive, aerospace, construction, and energy sectors are highlighted. The article concludes by anticipating future developments in this field, emphasizing the role of technology in shaping the future of high-strength cast iron.